Predictors of dropout in self‐guided internet‐delivered cognitive behaviour therapy for obsessive‐compulsive disorder: An exploratory study. - Wootton, Bethany M.; Melkonian, Maral; McDonald, Sarah; Karin, Eyal; Titov, Nickolai; Dear, Blake F. (British Journal of Clinical Psychology, 2025)
Objectives: Self‐guided internet‐delivered cognitive behaviour therapy (ICBT) is an effective treatment for obsessive‐compulsive disorder (OCD); however, there is little research investigating who dropouts of treatment. Therefore, the aim of this study was to conduct an exploratory study of predictors of dropout in self‐guided ICBT for OCD. Given that definitions of dropout vary across ICBT studies, we conceptualized dropout in multiple ways: (1) early dropout (proportion of participants who did not complete the pre‐treatment questionnaires); (2) proportion of participants who did not commence the intervention; (3) proportion of participants who did not complete the treatment; and (4) proportion of participants who did not complete the post‐treatment questionnaires. Method: This was a secondary data analysis of 323 participants with OCD symptoms who provided a successful screening assessment to commence an ICBT intervention. Binary logistic regression was used to predict dropout based on a number of exploratory variables. Results: Early dropout was predicted by the country of the participant (participants in the United Kingdom and India being more likely to dropout), as well as shorter symptom duration (explaining 7% of the variance). Medication use predicted non‐completion of the intervention with those taking medication for OCD being less likely to complete the treatment (explaining 3% of the variance). Completion of the post‐treatment questionnaires was predicted by higher contamination symptoms, lower depressive symptoms and higher pre‐treatment conscientiousness (explaining 13% of the variance). There were no significant predictors of treatment commencement. Conclusions: The study provides important preliminary information concerning which patients with OCD may be more likely to drop out of a self‐guided ICBT intervention.